2020
DOI: 10.1039/d0ta08067e
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of phase transitions on halide ratio in inorganic CsPb(BrxI1−x)3 perovskite thin films obtained from high-throughput experimentation

Abstract: In this communication we present the phase diagram of CsPb(BrxI1-x)3 (0≤x≤2/3, 300-585 K) obtained by high-throughput in-situ GIWAXS measurements of a combinatorial thin film library. We find that all compositions...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 27 publications
3
31
0
Order By: Relevance
“…The fact that it is cubic at a lower temperature than for CsPbI 3 is also consistent with the bromine influence over the transition temperature. Our cubic lattice parameter determined at 300 °C is close to the value reported in the literature for CsPb(I 1‐x Br x ) 3 with x∼1/3, that was a=6.170 Å , where no black phase was characterized upon heating for x<0.5, even after pre‐heat treatment of thin layers [14] . Yet, EDX analysis performed on our CsPbI 2 Br thin films, which showed 45(2) mol.% of I and 21(2) mol.% of Br, confirmed the close CsPbI 2 Br stoichiometry (experimentally CsPbI 2.05 Br 0.95 (see Figure S3b).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The fact that it is cubic at a lower temperature than for CsPbI 3 is also consistent with the bromine influence over the transition temperature. Our cubic lattice parameter determined at 300 °C is close to the value reported in the literature for CsPb(I 1‐x Br x ) 3 with x∼1/3, that was a=6.170 Å , where no black phase was characterized upon heating for x<0.5, even after pre‐heat treatment of thin layers [14] . Yet, EDX analysis performed on our CsPbI 2 Br thin films, which showed 45(2) mol.% of I and 21(2) mol.% of Br, confirmed the close CsPbI 2 Br stoichiometry (experimentally CsPbI 2.05 Br 0.95 (see Figure S3b).…”
Section: Resultssupporting
confidence: 87%
“…At 200 °C, peaks characteristic of the delta phase reappear in majority while those of the black phase disappear, in agreement with Nasstrom et al . who showed that thin films of CsPbI 3 cooled down in nitrogen showed a phase transformation from the beta to the delta phase at 184 °C [14] . Although previous studies performed on CsPbI 3 powders heated up in closed capillary showed that it can then be possible to obtain the gamma phase at RT, thin films are more constrained and can behave differently [9] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using an inkjet printing process with multiple printheads, it is possible to achieve this. [26][27][28] Inkjet printing as such has already been successfully used as a deposition method for organic semiconductors, [29] inorganic semiconductors, [30] and metal inks [31][32][33] for the fabrication of various electronic and optoelectronic devices. [34][35][36][37] More recently, inkjet printing has also been successfully used to deposit metal halide perovskites and perovskite nanocrystalbased optoelectronic devices such as solar cells, [38] LEDs, [39] and photodetectors.…”
Section: Introductionmentioning
confidence: 99%
“…[42,43] Moreover it is also an industrially mature and scalable, digital production technology, with the ability to be implemented in high-throughput and large-area industrial-scale production processes. [44] By now combining (at least) two printheads during printing, the simultaneous deposition of (at least) two inks within one coating process is possible and this combinatorial method has been used previously to screen material compositions [26][27][28] for application in solar cells. [45,46] In this way, the mixing of ink droplets during deposition on the substrate serves as a combinatorial synthesis and structuring approach, producing a precise ionic composition of the perovskite precursors.…”
Section: Introductionmentioning
confidence: 99%